Peningkatan kemandirian ekonomi perempuan melalui pelatihan konten kreator online - Rina Septiriana; Tursina Tursina; Yulianti Yulianti; Helen Sastypratiwi; Izuardo Zulkarnain (Universitas Hamzanwadi, 2026)
This Community Service (PKM) activity aims to improve digital literacy and economic independence of women in Bengkayang Regency through content creator and online business training. The activity was carried out on August 11, 2025 at the Hall of the Bengkayang Regency Library and Archives Service involving 30 female participants from various professional backgrounds, namely housewives (60%) and private sector workers (40%), with an age range of 25 to 45 years. The methods used include material presentation, hands-on workshop, and interactive discussion sessions. Training materials include product photography techniques using smartphones, use of Canva and CapCut applications, effective copywriting, social media marketing strategies, and entrepreneurial mindset building. The results showed that 100% of participants successfully practiced the material by creating their first product promotional content. This activity proved effective in improving participants' digital skills and providing a strong foundation for their online business development.